Pre Cal.

posted by .

Find three geometric means betwee -sqrt(2) and -4sqrt(2).

A: 2, -2sqrt(2), 4

Is 6 sqrt(2)+ 6 + 3sqrt(2)+... a convergent series?

A: Yes.

Is 1 + 3(1/2) + 9(1/2)^2 + 27(1/2)^3 +... a divergent series?

A: Yes.

Are these right?

  • Pre Cal. -

    All correct!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  2. MATH

    1/(X^-2Y)-1(XY^-2)=____ XY (square root of 84 - square root of 5.25) I don't understand the first equation. sqrt(84)=sqrt(4*21)=sqrt(16*5.25)=4sqrt(5.25) so sqrt(84)-sqrt(5.25)= 4sqrt(5.25)-sqrt(5.25)=3sqrt(5.25)
  3. calc check: curve length

    Find the length of the curve y=(1/(x^2)) from ( 1, 1 ) to ( 2, 1/4 ) [set up the problem only, don't integrate/evaluate] this is what i did.. let me know asap if i did it right.. y = (1/(x^2)) dy/dx = (-2/(x^3)) L = integral from a …
  4. Algebra

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  5. Algebra - sqrts

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  6. Advanced Math

    Can someone check these for me? Please? Use half-angle identity to find the exact value of cos165 degrees. (-1/2) sqrt(2+sqrt(3)) Write the equation 2x+3y-5=0 in normal form. (-2sqrt(13)/13)x- (3sqrt(13)/13)y+ (5 sqrt (13)/13) = 0
  7. Pre Cal.

    1. Use half-angle identity to find the exact value of cos165. MY ANSWER: (-1/2)sqrt(2+sqrt(3)) 2. Solve 2 sin x + sqrt(3) < 0 for 0<= x<2pi. MY ANSWER: (4pi/3)< x < (5pi/3) 3.Write the equation 2x+ 3y-5=0 in normal form?
  8. Pre-Cal

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  9. Pre-Cal(Urgent)

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …
  10. Pre-Cal

    Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were wrong. …

More Similar Questions